Subtle clinical signs of a meningioma in an adult: a case report - Marchand, Andrée-Anne (BioMed Central, 2014)
BACKGROUND: Meningiomas are the most common brain tumor in the adult population. This case report describes the epidemiology, the clinical presentation as well as the current treatment options for this condition. CASE PRESENTATION: A 49 year-old man attended a chiropractic clinic with non-specific chronic low back pain. Upon the history taking and the systems review, he reported a loss of both smell and taste for which investigations conducted by two different otolaryngologists did not yield a specific diagnosis. The patient was referred to a neurologist who ordered a computer tomography scan that eventually revealed a compression brain tumor. Brain tumors can produce a large variety of clinical presentations, such as upper motor neuron lesion symptoms, altered consciousness or vital functions which are easy to identify. However, subtle signs, such as those presented in this case, can be neglected. CONCLUSION: Clinicians should be aware of uncommon clinical presentations including cranial nerve or neurological dysfunction and refer their patient to a specialist when detected.